The Arabidopsis demethylase REF6 physically interacts with phyB to promote hypocotyl elongation under red light - Yan Yan; Jiaping Zhu; Qi Qiu; Jigang Li; Xiaofeng Cao; Xian Deng (Proceedings of the National Academy of Sciences, 2025)
The plant photoreceptor phytochrome B (phyB) mediates the responses of plants to red (R) light. Trimethylation of histone H3 at Lys27 (H3K27me3) plays a crucial role in governing gene expression and controlling the response of plants to environmental changes. However, how dynamic H3K27me3 mediates plant response to R light is poorly understood. Here, we report that RELATIVE OF EARLY FLOWERING 6 (REF6), an H3K27me3 demethylase, promotes hypocotyl elongation under R light in Arabidopsis . Upon exposure to R light, REF6 preferentially interacts with the active Pfr form of phyB. Consequently, phyB enhances REF6 accumulation and its binding ability, which are necessary for inducing cell-elongation-related genes from open chromatin, ensuring normal plant growth under prolonged light exposure. Moreover, REF6 acts together with the phyB-PIF4 module to mediate light regulation of hypocotyl growth. These findings provide insights into the understanding of how phytochromes, epigenetic factors, and transcription factors coordinately control plant growth in response to changing light environment.